The first man - Khan, S (Goodword Books: New Delhi, 2010)
The First Man is a part of the Quran Stories for Little Hearts series by Khan Saniyasnain. This beautifully illustrated children's book tells the story of the creation of Prophet Adam, the first man, as narrated in the Quran. It introduces young readers to Adam's role as the first human and prophet, his life in the Garden of Eden, and his relationship with Allah. Through simple language and vivid imagery, the story teaches children about the importance of obedience, gratitude, and seeking forgiveness. It's an engaging and educational read that imparts valuable lessons from Islamic teachings to young minds.